Long-term stability of intracortical recordings using perforated and arrayed Parylene sheath electrodes. (7th November 2016) - Hara, Seth A; Kim, Brian J; Kuo, Jonathan T W; Lee, Curtis D; Meng, Ellis; Pikov, Victor
Abstract: Objective . Acquisition of reliable and robust neural recordings with intracortical neural probes is a persistent challenge in the field of neuroprosthetics. We developed a multielectrode array technology to address chronic intracortical recording reliability and present in vivo recording results. Approach. The 2 × 2 Parylene sheath electrode array (PSEA) was microfabricated and constructed from only Parylene C and platinum. The probe includes a novel three-dimensional sheath structure, perforations, and bioactive coatings that improve tissue integration and manage immune response. Coatings were applied using a sequential dip-coating method that provided coverage over the entire probe surface and interior of the sheath structure. A sharp probe tip taper facilitated insertion with minimal trauma. Fabricated probes were subject to examination by optical and electron microscopy and electrochemical testing prior to implantation. Main results. 1 × 2 arrays were successfully fabricated on wafer and then packaged together to produce 2 × 2 arrays. Then, probes having electrode sites with adequate electrochemical properties were selected. A subset of arrays was treated with bioactive coatings to encourage neuronal growth and suppress inflammation and another subset of arrays was implanted in conjunction with a virally mediated expression of Caveolin-1. Arrays were attached to a custom-made insertion shuttle to facilitate precise insertion into the rat motor cortex. Stable electrophysiological recordings were obtained during the period of implantation up to 12 months. Immunohistochemical evaluation of cortical tissue around individual probes indicated a strong correlation between the electrophysiological performance of the probes and histologically observable proximity of neurons and dendritic sprouting. Significance. The PSEA demonstrates the scalability of sheath electrode technology and provides higher electrode count and density to access a greater volume for recording. This study provided support for the importance of creating a supportive biological environment around the probes to promote the long-term electrophysiological performance of flexible probes in the cerebral cortex. In particular, we demonstrated beneficial effects of the Matrigel coating and the long-term expression of Caveolin-1. Furthermore, we provided support to an idea of using an artificial acellular tissue compartment as a way to counteract the walling-off effect of the astrocytic scar formation around the probes as a means of establishing a more intimate and stable neural interface.